AKTIFITAS BURUH KARYA SENI GRAFIS - ANDREA VENANDRO, Dr. Budiwirman, M.Pd., Drs. Irwan, M.Sn. (Universitas Negeri Padang, 2018)
This work examines the activities of labor and the problems of laborers, workers consist of several parts, farm laborers, factory workers, laborers or unskilled laborers, and other workers, the problem of the workers' scope of social status, and work in life, for visualization labor activities in graphic arts.The method and process of work used in the creation of graphic art works through several stages: (1) preparation, (2) Elaboration, (3) Synthesis, (4) Realization of Concepts, (5) Settlement. And the last is the final exhibition of works, in the creation of works of labor activities in the graphic arts the author uses high printing techniques and the work of the writer clichés with hardboard and cut using carving tools.The results of visualization of labor activities in graphic arts are in the form of 10 works with the title: (1) No 10, (2) Bone from Wood, (3) Head protection, (4) Dminor, (5) Dmayor, (6) women, ( 7) Women I, (8) Men, (9) Men I (10) sow seeds.Keywords: human, social, labor activities, work